1976
DOI: 10.1128/jcm.3.3.264-271.1976
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pseudomonas aeruginosa infections: determination by pyocin typing

Abstract: The epidemiology of hospital infections due to Pseudomonas aeruginosa was investigated by pyocin typing. The typing method, which determined the pyocin activity of clinical isolates of P. aeruginosa on 27 indicator strains, was 43.7% reproducible, but elimination of 9 indicator strains doubled the reproducibility and yielded more readable pyocin inhibition zones. Seventy-eight of 1,084 isolates (7.2%) were untypable. In the second part of the study, P. aeruginosa was isolated from 110 patients (5.4% of all adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…They also affirmed that the hands are a major vehicle for the transfer of Pseudomonas bacteria and implicated bar soap in its spread. 14 Other groups of researchers have found that bacteria survive on soap bars in continuous use in public lavatories, even when cultured 48 hours following their last use. 15,22 The role of the soap dish in infection control has also been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also affirmed that the hands are a major vehicle for the transfer of Pseudomonas bacteria and implicated bar soap in its spread. 14 Other groups of researchers have found that bacteria survive on soap bars in continuous use in public lavatories, even when cultured 48 hours following their last use. 15,22 The role of the soap dish in infection control has also been studied.…”
Section: Discussionmentioning
confidence: 99%
“…13 Much studies have been written and debated regarding the use of bar versus liquid skin cleansers in relation to infection control. 7, [14][15][16][17][18][19][20][21][22] In this study, the aim was to detect and compare bacterial contamination of soap bars and liquid soaps.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, during this period, it was found that R-type pyocins have a more efficient killing activity than headless mutants of a related phage, supporting the hypothesis that these particles are not simply defective prophages but evolved weapons ( Shinomiya and Shiga, 1979 ). Additionally, their advantage for medical use was explored, employing pyocins for P. aeruginosa typing ( Farmer and Herman, 1969 ; Rose et al, 1971 ; Edmonds et al, 1972 ; Lovrekovich et al, 1972 ; Jones et al, 1974 ; Duncan and Booth, 1975 ; Bruun et al, 1976 ; Fyfe et al, 1984 ; Schable et al, 1986 ) as well as a potential treatment against P. aeruginosa infections ( Merrikin and Terry, 1972 ; Haas et al, 1974 ). In addition to all these findings, a new type of phage tail-like pyocin, the F-type, was discovered ( Takeya et al, 1969 ; Govan, 1974b ; Kuroda et al, 1979 ; Kuroda and Kageyama, 1979 , 1981 ; Michel-Briand and Baysse, 2002 ; Saha et al, 2023 ).…”
Section: A Brief History Of Ecissmentioning
confidence: 99%
“…The usage of eCISs for potential biotechnological applications is not a recent concept. These particles were already used in the 1970s as a tool for P. aeruginosa typing or “fingerprinting” to better identify, investigate and control outbreaks ( Farmer and Herman, 1969 ; Rose et al, 1971 ; Edmonds et al, 1972 ; Lovrekovich et al, 1972 ; Jones et al, 1974 ; Duncan and Booth, 1975 ; Bruun et al, 1976 ; Fyfe et al, 1984 ; Schable et al, 1986 ). Furthermore, as multi-drug resistant bacterial infections are becoming more frequent and more difficult to treat, the high specificity of eCISs, specifically R-tailocins, has interesting potential for medical applications in the treatment of nosocomial P. aeruginosa infections.…”
Section: Biotechnological Applications Of Ecissmentioning
confidence: 99%